Flood Discharge Estimation in Ungauged Basins Using Synthetic Unit Hydrographs and GIS - Kesgin, Erdal (Fırat Üniversitesi, 2025)
Flooding refers to the adverse effects caused by rivers overflowing their banks due to various reasons, affecting surrounding land, residential areas, and infrastructure. At the watershed scale, particularly in cases where flow monitoring stations are absent, hydrographs must be generated to analyze rainfall-runoff relationships for flood assessments. This study aims to generate synthetic hydrographs, analyze rainfall-runoff relationships, and estimate flood discharges for different return periods in a predominantly forested sub-watershed located in the Sarıyer district of Istanbul. The study analyzed extreme rainfall by calculating 24-hour maximum values for return periods of 2 to 100 years using four common probability distribution functions: Normal, Log-Normal, Log-Pearson Type III, and Gumbel. Among these methods, Log-Pearson Type III yielded higher rainfall values, and given the extreme nature of floods, it was preferred for discharge calculations. In the second stage of the study, flood hydrographs specific to the watershed were generated for different return periods using the DSI, Mockus, and Snyder unit hydrograph methods, incorporating watershed physical characteristics and dimensionless unit hydrograph coordinates. The results indicated that the DSI and Mockus methods produced similar and higher peak discharge values (Q??? = 67.44 and 63.76 m³/s, T=100 years), whereas the Snyder method resulted in lower peak discharge (Q??? = 32.17 m³/s for T = 100 years) but a longer hydrograph duration. Overall, it was concluded that the DSI and Mockus methods are more suitable for flood analysis in forested and relatively small watersheds (?10 km²) due to their effectiveness in generating hydrographs for flood assessments. This study contributes to the literature by offering a comparative evaluation of three widely used synthetic unit hydrograph methods, specifically tailored for a forest-dominated ungauged basin in an urbanizing region of Istanbul, providing actionable insights for flood estimation in data-scarce, forested urban catchments.

Taşkın, bir akarsuyun çeşitli nedenlerle yatağından taşarak çevresindeki arazi, yerleşim alanları, altyapı tesisleri ve ekosistem üzerinde oluşturduğu olumsuz etkiler olarak tanımlanabilir. Havza ölçeğinde, özellikle akım gözlem istasyonlarının bulunmadığı durumlarda, taşkın analizleri için yağış-akış ilişkileri için hidrograflar oluşturulmalıdır. Bu çalışmada, İstanbul, Sarıyer ilçesinde yer alan ve büyük ölçüde ormanlık niteliğindeki bir alt havza için sentetik hidrografların oluşturulması, yağış-akış ilişkilerinin analiz edilmesi ve farklı tekerrür aralıkları için taşkın debilerinin hesaplanması amaçlanmıştır. Ekstrem yağış analizleri kapsamında, Normal, Log-Normal, Log-Pearson Tip III ve Gumbel olasılık dağılım fonksiyonları kullanılarak çeşitli tekerrür aralıkları (T = 2, 5, 10, 25, 50, 100 yıl) için 24 saatlik maksimum yağış değerleri hesaplanmıştır. Log-Pearson Tip III yöntemiyle elde edilen yağış değerlerinin daha yüksek olduğu belirlenmiş ve taşkınların ekstrem doğası göz önüne alındığında, debi hesaplamalarında bu yöntemin kullanılması tercih edilmiştir. Çalışmanın ikinci aşamasında, havzanın fiziksel özellikleri ve boyutsuz birim hidrograf koordinatları kullanılarak, DSI, Mockus ve Snyder birim hidrograf yöntemleri aracılığıyla çeşitli tekerrür aralıkları için havzaya özgü taşkın hidrografları üretilmiştir. Sonuçlar, DSI ve Mockus yöntemlerinin birbirine yakın ve yüksek pik debi değerleri ürettiğini (T = 100 yıl için Q??? sırasıyla 67,44 ve 63,76 m³/s), buna karşın Snyder yönteminin daha düşük pik debi değerleri (T = 100 yıl için Q??? = 32,17 m³/s) ancak daha uzun süreli bir hidrograf oluşturduğunu ortaya koymuştur. Genel olarak, DSI ve Mockus yöntemlerinin, ormanlık ve nispeten küçük havzalarda (?10 km²) taşkın analizlerinde kullanılacak hidrografın oluşturulması açısından daha uygun olduğu sonucuna varılmıştır. Bu çalışma, İstanbul'un kentleşen bir bölgesinde, ormanlık alanların hâkim olduğu ölçüm istasyonu bulunmayan bir havza için özel olarak uyarlanmış üç yaygın sentetik birim hidrograf yönteminin karşılaştırmalı bir değerlendirmesini sunarak, veri yetersizliği yaşanan bölgelerde hidrolojik modelleme konusunda literatüre katkı sağlamaktadır.
Akım Gözlemi Olmayan Havzalarda Sentetik Birim Hidrograf Yöntemleri ve CBS Kullanılarak Taşkın Debilerinin Tahmini
Keywords: Civil Engineering (Other); İnşaat Mühendisliği (Diğer)